Of MIs and Men—A Historical Perspective on the Diagnostics of Acute Myocardial Infarction - Cervellin, Gianfranco; Lippi, Giuseppe (Seminars in Thrombosis and Hemostasis, 2014)
The history of myocardial infarction (MI) diagnostics has gone through a continuous evolution over the past century, when several new discoveries have contributed to remarkably increase the number of patients appropriately diagnosed with this condition. The tale “of MIs and Men” displays rather a long history, since atherosclerosis was found to be present in humans several centuries before modern civilization and the identification of the most prevalent risk factors. It was only at the end of the 19th century and at the beginning of the 20th century that the physicians acknowledged that MI is principally sustained by coronary thrombosis, and that the clinical picture of MI could be subsequently confirmed at autopsy. With the first description of the electrocardiogram (ECG) in the 1910s and 1920s, the history of modern MI diagnostics really began. Additional important discoveries followed, which are mainly represented by radiography, echocardiography, computed tomography, and magnetic resonance imaging of the heart. Another major breakthrough occurred at the down of the third millennium, with the development of commercial immunoassays for the measurement of cardiac troponin I and T, which represent now the cornerstones for identifying any kind of myocardial injury, thus including MI. The major advancements in the understanding of MI pathophysiology and the progressive introduction of efficient diagnostic tools will be described and discussed in this narrative historical review.
Keywords: myocardial infarction; acute coronary syndrome; history; electrocardiogram; biomarkers